Pattern of infertility among infertile couples in a tertiary health institution in Bayelsa State, South-South Nigeria - Oriji, Peter Chibuzor; Kiridi, Enefia Kelvin; Ubom, Akaninyene Eseme; Okoye, Chukwunonso Nnamdi; Oriji, Victoria Komonibo; Awotundun, Benjamin (International Journal of Scientific Reports, 2022)
Background: Infertility is a socially distressing medical condition that remains a public health concern in many developing countries, including Nigeria. The objective of the study was to evaluate the pattern of infertility among infertile couples in a tertiary hospital in South-South Nigeria. Methods: A retrospective, descriptive, cross-sectional study of infertile couples evaluated at the Infertility Clinic of the Federal Medical Centre, Yenagoa, Bayelsa State, South-South Nigeria, between January and December, 2021, was conducted. Case records of all the infertile couples evaluated during the study period were retrieved, and relevant data were extracted from the case records using a pre-designed proforma. Data obtained was analysed using Statistical Product and Service Solutions for Windows® version 25 (SPSS Inc.; Chicago, USA). Results: The incidence rate of infertility was 18.2%. Tubal factor was the most common (104, 55.6%) cause of infertility, with tubal blockage being the commonest (92, 49.2%) tubal pathology. Male factor was implicated in 81, 43.3%, of the cases, a combination of male and female factors in 45, 24.1%, while 5, 2.7%, of the cases were unexplained. Female factor alone was responsible for infertility in 101, 54.0%, of the cases, while male factor alone was identified in 36, 19.2%, of the cases. Conclusions: Our study’s incidence rate for infertility was similar to those reported in other studies in our region. To reduce the incidence of infertility, social reorientation to improve sociocultural practices and poor health-seeking behaviour of couples, should be pursued vigorously.